2018
DOI: 10.1097/mph.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution Inflammatory Syndrome After DLI in a SCID Patient After Hematopoetic Stem Cell Transplantation

Abstract: Immune reconstitution inflammatory syndrome (IRIS) is a clinical condition emerging after immune recovery of an immunocompromised status, mostly in human immunodeficiency virus infected patients but also in several other settings, such as the recovery from the severe combined immunodeficiency status after hematopoietic stem cell transplantation. Herein, we report a patient transplanted for severe combined immunodeficiency who developed IRIS for 2 times, namely shortly after transplantation and after donor lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…Unmasking IRIS refers to the worsening of a pre-existing infection that has not been detected during the process of immune recovery, whereas paradoxical IRIS refers to the worsening of a confirmed pre-existing infection. Nine cases of paradoxical IRIS after HSCT were reported, and Mycobacterium was the most common pathogen ( 3 , 4 , 11 , 12 ). We speculate that the IRIS of our patient was related to immune dysregulation following successful HSCT, including pre-existing BCG infection, immune reconstitution after HSCT, and withdrawal of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmasking IRIS refers to the worsening of a pre-existing infection that has not been detected during the process of immune recovery, whereas paradoxical IRIS refers to the worsening of a confirmed pre-existing infection. Nine cases of paradoxical IRIS after HSCT were reported, and Mycobacterium was the most common pathogen ( 3 , 4 , 11 , 12 ). We speculate that the IRIS of our patient was related to immune dysregulation following successful HSCT, including pre-existing BCG infection, immune reconstitution after HSCT, and withdrawal of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Not all IRIS requires treatment, and the majority of patients with IRIS have a good prognosis ( 5 , 11 14 ). In addition to glucocorticoids and immunosuppressants, other treatment for IRIS includes non-steroidal anti-inflammatory drugs (NSAIDs) and immunosuppressants ( 11 , 15 , 16 ). Anti–IL-6 agent tocilizumab has also been used to treat IRIS due to elevated inflammatory factors ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…IRIS occurs most commonly as inflammatory manifestations during anti-retroviral treatment of human inmmunodeficiency virus (HIV) (Martin-Blondel et al, 2012). Recent reports and studies have also observed chronic disseminated candidiasisrelated IRIS in other immunocompromised conditions such as in haematological malignancies and after stem cell transplantation (Chaussade et al, 2012;Jang et al, 2018;Kocacik Uygun et al, 2018). The pathogenesis of this phenomenon is thought to be due to rapid recovery and overactive response of T lymphocytes and granulocytes during adequate antimicrobial treatment of the infection (Chaussade et al, 2012;Jang et al, 2018;Martin-Blondel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As the patient's immune system improves, IRIS may lead to a paradoxical clinical deterioration when intense inflammatory infiltrates are formed to eradicate an underlying subclinical infection. IRIS should be considered when a patient has had an infection and the following three criteria are met: (a) new or worsening clinical or radiologic manifestations consistent with an inflammatory process occur (eg, signs of elevated intracranial pressure, cerebrospinal fluid pleocytosis, and contrast material-enhancing leptomeninges or masses manifest); (b) symptoms occur during receipt of appropriate antimicrobial therapy, without evidence of newly acquired infection; and (c) laboratory results indicate negative culture or stable or reduced biomarkers for the initial infection (3,8,13,14).…”
Section: Principles Of Hsctmentioning
confidence: 99%